Driving Sustainable Change: Behavior and Environmental Awareness in the Case of the Philippines - Solina , Alfe M.; Ocampo , Liane Vina G. (Research Advances in Environment, Geography and Earth Science Vol. 5, 2024)
The increasing emphasis on environmental awareness becomes essential in a global landscape where environmental decline jeopardizes our future progress. This raised awareness instills a sense of responsibility towards the environment, prompting consumers to actively support businesses aligned with sustainability principles. Ultimately, environmental consciousness serves as a driving force behind positive consumer outlooks on products and behaviors that contribute to ecological well-being. This chapter underscores the power of consumer behavior, particularly among the younger demographic, in advancing sustainability efforts for the future. Specifically, the paper explores the intersection of consumer behavior and environmental awareness within the context of the Philippines by examining various dimensions of environmental knowledge and attitudes toward sustainability in purchasing behavior. The study also highlights the urgency of addressing environmental degradation in the country by identifying sustainable solutions to combat these issues like deforestation, pollution, and climate change impacts. Through the study conducted among Filipino consumers, the research shed light on the current state of environmental awareness and eco-conscious purchasing behaviors. Despite gaps in perception and understanding, there is evidence of a growing inclination toward sustainability. Empowering consumers through education, targeted marketing strategies, and policy interventions to foster a greener future. Ultimately, the research emphasizes the influential role of consumer behavior in shaping environmental outcomes and advocates for efforts to accelerate the transition toward a more sustainable future.